Application of pcswmm for the 1?d and 1?d2?d modeling of urban flooding in damansara catchment, malaysia - Sidek L.M.; Chua L.H.C.; Azizi A.S.M.; Basri H.; Jaafar A.S.; Moon W.C. (MDPI, 2023)
Coupled with climate change, the urbanization?driven increase in the frequency and intensity of floods can be seen in both developing and developed countries, and Malaysia is no exemption. As part of flood hazard mitigation, this study aimed to simulate the urban flood scenarios in Malaysias urbanized catchments. The flood simulation was performed using the Personal Computer Storm Water Management Model (PCSWMM) modeling of the Damansara catchment as a case study. An integrated hydrologic?hydraulic model was developed for the 1?D river flow modeling and 1?D2?D drainage overflow modeling. The reliability of the 1?D river flow model was confirmed through the calibration and validation, in which the water level in TTDI Jaya was satisfactorily predicted, supported by the coefficient of determination (R2), NashSutcliffe model efficiency coefficient (NSE), and relative error (RE). The performance of the 1?D2?D model was further demonstrated based on the flood depth, extent, and risk caused by the drainage overflow. Two scenarios were tested, and the comparison results showed that the current drainage effectively reduced the drainage overflow due to the increased size of drains compared to the historic drainage in 2015. The procedure and findings of this study could serve as references for the application in flood mitigation planning worldwide, especially for developing countries. 2021 by the authors. Licensee MDPI, Basel, Switzerland.